The Correlation between Students’ Internet Activity Frequency and their Vocabulary Size at IAIN Bukittinggi - Muhammad Rizki ramadhan; Syahrul Syahrul (Journal of English Language and Education, 2021)
In this pandemic COVID-19, students were required to use internet in all of the activities in order to limit the face to face interaction. Students just stay at home and do online school by used internet. In internet, majority of the contents used English. Students who used internet got a lot of exposure to English vocabulary. In this research, researcher found some problem such as: there were some students used internet but their vocabulary still limited, and there were some students used internet and them had many vocabulary. In other hand, there were some students mastery vocabulary they easy to understand of point in internet. So researcher wanted to know was there correlation between students’ internet activity frequency and their vocabulary size. The researcher used the quantitative research. The design of this research was correlational research because it had the purpose to find out correlation between internet activity frequency and vocabulary size. The population in this research was 108 students that were the total of the students in the seventh semester in IAIN Bukittinggi. Researcher took 30% from population as sample of this research which was 33 students. To collect the data, this study used questioners and test. Based on the finding there was significant correlation between internet activities frequency and vocabulary size since sig values is smaller than alpha (0,0000010,3440). This means that the students’ internet frequency activity correlate with their vocabulary size. Second, there was positive correlation between both variables (+0.730). In other word, the more students have activity in the internet the better their vocabulary size. Third, the magnitude of the correlation was high (between 0.71—0.90). This means the more students use internet the more they are exposed to the English language since the Internet use English in majority, so that the students’ vocabulary size would improve. So if students frequent used internet, so their vocabulary will improve.